2017
DOI: 10.22159/ijpps.2017v9i2.15790
|View full text |Cite
|
Sign up to set email alerts
|

Sterols Bioactivity of Ruta Graveolens L. And Murraya Paniculata L.

Abstract: Objective: Ruta graveolens L. (R. graveolens) and Murraya paniculata L. (M. paniculata) are medicinal plants belonging to Rutaceae family have many uses in traditional medicine. The aim of the present study was to investigate sterols bioactivity of the two Rutaceae plant leaves.Methods: Sterols of the two Rutaceae plant leaves were identified using GC/MS. The antioxidant activities of the sterols of these herbs were evaluated by three different methods; free radical scavenging using 2,2′-Azino-bis (3-ethylbenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Among the different bioactive compounds present in this plant, phytosterols are known to present anticancer and dose-dependent anti-inflammatory activity. Baker et al proved the action of these substances present in R. graveolens extracts against colorectal cancer, breast cancer, lung cancer, and hepatocellular carcinoma tumor cells (HepG2) 9 . In this way, the effects of the extract of this plant have already been showed, now our study evaluated the cell-based effects of the homeopathic medicine and presented the cytotoxic mechanism against liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the different bioactive compounds present in this plant, phytosterols are known to present anticancer and dose-dependent anti-inflammatory activity. Baker et al proved the action of these substances present in R. graveolens extracts against colorectal cancer, breast cancer, lung cancer, and hepatocellular carcinoma tumor cells (HepG2) 9 . In this way, the effects of the extract of this plant have already been showed, now our study evaluated the cell-based effects of the homeopathic medicine and presented the cytotoxic mechanism against liver cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…To mitigate the cytotoxic effects and use as supportive care treatments, homeopathy has been frequently considered. Its use in oncology as supportive care is relatively recent 9 , with in vitro and in vivo publications being published and beginning to demonstrate the potential of homeopathic dilutions affecting cancer cells 7 . Therefore, there are still concerns about the way of action of homeopathic medicines in cancer cells and this study aimed to evaluate the effect of the homeopathic medicine Ruta D35 in human Hepatocellular Carcinoma cells (HepG2) through in vitro cytotoxicity tests.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, it has been reported that sterols from the leaves of M. paniculata inhibited the A549 cancer cells by 77.3 percent. [35] So, the further research work could be done to explore M. paniculata for the treatment of cancers.…”
Section: Anticancer Activitiesmentioning
confidence: 99%
“…The isolated sterol from MP leaves exhibited antitumor activity against cancer cell lines. The cytotoxic actions of sterols were determined by an MTT assay [48]. In one investigation, the cytotoxic effect of ethyl acetate extracts of MP leaves was investigated on human gingival fibroblasts and monocytes [49].…”
Section: Anticancer Activitymentioning
confidence: 99%